Predictors of virologic failure in HIV/AIDS patients treated with highly active antiretroviral therapy in Brasília, Brazil during 2002–2008 - Bello, Edson José Monteiro (2011)
Little data exists concerning the efficacy of the antiretroviral therapy in the Federal District in Brazil, therefore in order to improve HIV/AIDS patients’ therapy and to pinpoint hot spots in the treatment, this research work was conducted. Of 139 HIV/AIDS patients submitted to the highly active antiretroviral therapy, 12.2% failed virologically. The significant associated factors related to unresponsiveness to the lentiviral treatment were: patients’ place of origin (OR = 3.28; IC95% = 1.0–9.73; P = 0.032) and Mycobacterium tuberculosis infection (RR = 2.90; IC95% = 1.19–7.02; P = 0.019). In the logistic regression analysis, the remaining variables in the model were: patients’ birthplace (OR = 3.28; IC95% = 1.10–9.73; P = 0.032) and tuberculosis comorbidity (OR = 3.82; IC95% = 1.19–12.22; P = 0.024). The patients enrolled in this survey had an 88.0% therapeutic success rate for the maximum period of one year of treatment, predicting that T CD4+ low values and elevated viral loads at pretreatment should be particularly considered in tuberculosis coinfection, besides the availability of new antiretroviral drugs displaying optimal activity both in viral suppression and immunological reconstitution.